INOVASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN SUMBERLAWANG KABUPATEN SRAGEN (PROVINSI JAWA TENGAH) - Mursid, Joko; Haryanto, Aris Tri; Pramono, Joko (JI@P, 2023)
The purpose of this research is to describe the innovation of the District Integrated Administrative Service (DIAS) in Sumberlawang District, Sragen Regency. This type of research is a qualitative research with a case study approach. Data collection techniques used: in-depth interviews, documentation studies, and observation. Data validation uses: trustworthiness, transferability, and certainty. The data analysis technique uses an interactive model. The results of the study concluded that: (1) DIAS is a service innovation, has characteristics such as: as new knowledge, new ways, has new objects, requires new technology support, and is a form of new invention in sub-district organizations in providing services to the community; (2) Obstacles faced by Sumberlawang Sub-district, Sragen Regency in implementing DIAS innovation, among others: lack of skills and number of sub-district HR personnel to serve the community, lack of socialization to the community, budget support that has not been maximized. However, all these shortcomings are still within reasonable limits so that the implementation of the DIAS program can still be carried out; (3) The solutions taken to anticipate the obstacles faced by Sumberlawang Sub-district, Sragen Regency in implementing DIAS innovation, include: providing training for employees on the use of DIAS applications, increasing socialization about DIAS to the public, proposing additional budgets in the future, and making efficiency the existing budget for purposes deemed urgent to implement the DIAS program in order to keep it running. Keywords: Innovation, DIAS